2016
DOI: 10.1123/mc.2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Inhibition is Increased During a Secondary Cognitive Task

Abstract: The purpose of this study was to assess the effect of a cognitive task on motor cortex excitability and inhibition. Transcranial magnetic stimulation of the motor cortex was performed on 20 healthy individuals (18-24 years; 9 females) to measure motor evoked potentials (MEPs) and cortical silent periods at baseline, during, and following a secondary cognitive task. The MEP amplitude increased from 0.50 ± 0.09-0.87 ± 0.50 mV during a secondary cognitive task (p = .04), and returned to baseline (0.48 ± 0.31 mV; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, several studies have noted that cognitive challenges can magnify neuromuscular deficits in athletic tasks, even in groups of participants who did not sustain a recent concussion [9194]. This notion is further supported by recent transcranial magnetic stimulation studies that reported increased cortical inhibition during a dual task compared with a single task among healthy individuals [95, 96]. Such an observation may be owing to the inability of motor or attentional systems to properly allocate the necessary resources for optimal execution by motor and cognitive demands.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, several studies have noted that cognitive challenges can magnify neuromuscular deficits in athletic tasks, even in groups of participants who did not sustain a recent concussion [9194]. This notion is further supported by recent transcranial magnetic stimulation studies that reported increased cortical inhibition during a dual task compared with a single task among healthy individuals [95, 96]. Such an observation may be owing to the inability of motor or attentional systems to properly allocate the necessary resources for optimal execution by motor and cognitive demands.…”
Section: Discussionmentioning
confidence: 76%